Conceptual post occupancy evaluation model for neighborhood assessment towards sustainable urban development - Yaman, Rostam; Yaman, Rostam; Thadaniti, Suwattana; Adnan, Hamimah; Ahmad, Noraini (2016)
This research present the preliminary study of a post occupancy evaluation (POE) model on neighborhood assessment criteria towards sustainable urban development. The aim of the study is to develop a POE model based on sustainable pillar dimensions. The preliminary objective of this study is to identify and formulate a theoretical framework of POE towards sustainable neighborhood development and to implement the model in evaluating Green Building Index (GBI) certified neighborhood in Malaysia. The survey questionnaires and interviews are used in this research in order to gather experts’ opinion regarding the proposed POE model for sustainable neighborhood development for the certified GBI neighborhood project. The significant contribution of this study is the theoretical POE model towards sustainable neighborhood development for Malaysia and similar development phenomenon in ASEAN nations and another country throughout the world.